Latest Developments in Robotic Percutaneous Coronary Interventions - Arif A Khokhar; Andrea Marrone; Konstantinos Bermpeis; Eric Wyffels; Maria Tamargo; Francisco Fernandez-Avilez; Rossella Ruggiero; Adriana Złahoda-Huzior; Francesco Giannini; Aleksander Zelias; Ryan Madder; Dariusz Dudek; et al. (Interventional Cardiology: Reviews, Research, Resources)
Since the first robotic-assisted percutaneous coronary intervention procedure (R-PCI) was performed in 2004, there has been a steady evolution in robotic technology, combined with a growth in the number of robotic installations worldwide and operator experience. This review summarises the latest developments in R-PCI with a focus on developments in robotic technology, procedural complexity, tele-stenting and training methods, which have all contributed to the global expansion in R-PCI.